Project ease program evaluation: basis for an enhanced implementation - Canete, Jesselle I. (Parañaque City: Olivarez College, 2012)
This study sought to evaluate the effectiveness of project EASE implemented at Paranaque National High School {96} Don Galo Annex as perceived by the teachers, parents, and students to serve as basis for a proposed program implementation enhancement. It sought to answer the following questions: What is the level of effectiveness of Project EASE as perceived by teachers, parents and students in terms of; Objectives Curriculum Teachers Instructional materials Students admission and eligibility requirements Learning system Procedure Orientation and training Planning and preparation Implementation Evaluation Is there a significant difference in the three groups of respondents perceived level of effectiveness of the program? What are the problems encountered in the implementation of the program? Based on the findings of the study, what program implementation enhancement can be proposed? Methodology The descriptive-survey method of research was used in this investigation because this type of research describes, records, analyzes, and interprets the existing conditions (Son, 2009). This method of research focuses on the present conditions of projects, programs and activities. Respondents There were three groups of respondents for this program evaluation. They were five teachers, thirty-five (35) parents and sixty-five (65) students. Instrument To gather data, the researcher used a questionnaire with a rating scale and a checklist. A unstructured interview was also undertaken for the same purpose. Statistical Treatment The frequency and / or percentage distribution were used to determine the proportion of the respondents falling under certain categories. The weighted mean was determined to know the respondents{92} perceived level of effectiveness of Project Analysis of Variance (ANOVA) was applied to determine whether there was a significant difference on the levels of perceptions on the effectiveness of Project EASE among the teachers, parents and students {96} respondents. Findings The findings were the following; On the Respondents{92} Perception on the Level of Effectiveness of Project EASE: The project objectives had a overall weighted mean of 3.21 interpreted as Very Much Effective (VME) The curriculum component had an overall weighted mean of 3.12 interpreted as Very Effective (VE). The EASE teachers were found to be Very Much Effective (VME) as evidenced by an overall weighted mean of 3.49. The instructional materials were rated with an overall weighted mean of 3.31. interpreted as Very Much Effective (VME). The students{92} admission and eligibility requirements were rated with an overall weighted mean of 3.04 considered as Very Effective (VE). The learning system component was found to be Very Effective (VE) as proven by its overall weighted mean of 2.98. 1.7.1. The orientation and training under procedure got an overall weighted mean of 3.22 interpreted as Very Much Effective (VME). 1.7.2. The preparation and planning which were also under procedure were found to be Very Much Effective (VME) with an overall weighted mean of 3.24. 1.8. The implementation was rated with an overall weighted mean of 3.23 considered as Very Much Effective (VME) 1.9.The evaluation had an overall weighted mean of 3.15 interpreted as Very Effective (VE). On the Difference of Perceptions on Program Level of Effectiveness. There was no significant difference on the perceptions of the teachers, parents and students on the level of effectiveness at 0.05 level of significance because the computed F for the components such as the objectives, curriculum, teachers, instructional materials, students admission and eligibility requirements, procedure: orientation and training, planning and preparation, and implementation were lower than 3.09. At the outset, the null hypothesis that there was no significant difference among the perceptions of teachers, parents and students was accepted. However, the computed F for learning system and evaluation were 3.10 and 4.83 respectively which were higher than the F value at 0.05 level of significance which is 3.09. Consequently, the null hypothesis that there was a significant difference among the perceptions of teachers, parents and students was officially rejected. On the Respondents{92} perceived gains of benefits from the program of the benefits cited in the study, the provision of free learning materials ranked first among the perceived benefits with a percentage of 86.28 while the provision that students have less financial burden for transportation and school allowance is the least among the gains or benefits had a percentage 57.80. On the perceived problem encountered Majority of the respondents considered their primary problem with a percentage of 61.11 the seeming uncertainly of the teachers if students answered by themselves the lessons in the modules at home as. Ranked second at a percentage of 58.82 was the perception that some extra-curricular activities in the regular high school were not participated in nor enjoyed by the EASE students. Ranked 3.5 were problems about parents tending to become unmindful of the child{92}s study habits since modules were provided and students{92} lack of effort to return to regular high school because they enjoyed the minimal school attendance in EASE. Both had a percentage of 51.96. Among the ten (10) problems cited in the study, ranking least at 9.5 was some teachers{92} tendency to depend totally on the lessons in the modules and the inadequacy of learning modules. Both also had a percentage of 40.20. Conclusions Based on the findings, the following conclusions were drawn out. The on the objects were successfully achieved and deemed appropriate for the program itself. Moreover , the people concerned truly realized the significance of the program. The curriculum has addressed the learning needs of the students. The teachers were mindful of their teaching duties and responsibilities. The instructional materials were appropriate to the level of understanding and learning styles of students. The students admission and eligibility requirements justify inclusion of students in the project. The learning system was accepted and by the teachers, parents and students. 1.7.1 Orientation and training of people concerned is definitely needed before the start of the program 1.7.2Preparation and planning in a project cannot be done away with. 1.8The implementation was carried out properly with no significant problems arose. 1.9The evaluation component of the program was able to identify on the objects the strengths and weaknesses of the project if there were any. 2.Teachers, parents and students have similar perceptions on the objects, curriculum, teachers, instructional materials, students admission and eligibility requirements, procedure: orientation and training, planning and preparation, and implementation except in learning system and evaluation. 3.The program was accepted to be beneficial since that majority of the teacher, parents and students perceived it to be so. 4.Like any other DepEd program, project and activities, project EASE is not a perfect program. It is expected that some problems would be encountered in the implementation of programs, projects and activities. Recommendations Considering the findings and conclusion of this study, the following are hereby recommended by the researcher. That the objects of the program be sustained. That the project EASE curriculum be used continuously while project EASE is still in place. That the teachers be given more opportunities for professional development and incentives commensurate to the efforts exerted in the program. That the instructional materials be continuously used and as much as possible be enriched and integrated with current technology. Although the students admission are just appropriate, there is still a need for the participating students to undergo the reading ability test, math and coping skills assessment to determine their readiness for independent learning. That as far as the learning system is concerned, there is a need for the time allotment to be continuously adhered to, books be equally provided, home tutoring be resorted to, and two-days-a-week school days be sustained. .1 That orientation and training should not be neglected especially before the start of the program.
1.7.2That more time be allotted for preparation and planning so that all components can be thoroughly looked into 1.8That the manner of implementation be used as model in future programs, projects and activities of DepEd. 1.9That evaluation instruments be utilized and applied to programs, projects and activities whose nature is similar to Project EASE. 2.That perceptions of teachers, parents and students be considered in assessing future programs, projects and activities so as to have a true picture of the program. 3.That program EASE be supported by all sectors especially the teachers, parents and students and other members of the community. 4.That careful and through preparation and planning be done in any programs, projects and activities to be launched. 5.That the proposed EASE program implementation enhancement as recommended be concretely actualized in the school system.
Master Thesis